1998
DOI: 10.1136/sti.74.2.95
|View full text |Cite
|
Sign up to set email alerts
|

Oral sex and transmission of non-viral STIs

Abstract: Objectives:To review the literature on the role of oral sex in the transmission of non-viral sexually transmitted infections (STIs). Method: A Medline search was performed using the keywords oro-genital sex, and those specific to each infection. Further references were then taken from each article read. Conclusions: Oral sex is a common sexual practice between both heterosexual and homosexual couples. Oro-genital sex is implicated as a route of transmission for gonorrhoea, syphilis, Chlamydia trachomatis, chan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
120
0
1

Year Published

2000
2000
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 165 publications
(123 citation statements)
references
References 98 publications
2
120
0
1
Order By: Relevance
“…Protozoan infections of the oral cavity have been reported in patients with and without periodontal disease [1,5,68]. There is evidence for the transmission of non-viral STIs by oral sex [21].…”
Section: Discussionmentioning
confidence: 99%
“…Protozoan infections of the oral cavity have been reported in patients with and without periodontal disease [1,5,68]. There is evidence for the transmission of non-viral STIs by oral sex [21].…”
Section: Discussionmentioning
confidence: 99%
“…5 Several studies suggest that the resurgence of bacterial STDs (syphilis, gonorrhea, and chlamydia) may be partially due to the practice of oral sex by MSM, often to substitute for, or avoid anal sex. 6 A separate survey conducted during 2007-2010 found that 33% of teenage girls and boys aged 15-17 years reported having had oral sex with a partner of the opposite sex. Studies have shown that the risk of getting HIV from having oral sex with an infected partner (either giving or getting oral sex) is much lower than the risk of getting HIV from anal with an infected partner.…”
Section: Discussionmentioning
confidence: 99%
“…11 The oral mucosa is commonly affected as a consequence of orogenital contact. [12][13][14] Chancres contain many viable treponemes, and are thus highly infectious. In men, oral chancres tend to arise on the upper lip, while in women, the lower lip is more commonly affected.…”
Section: Discussionmentioning
confidence: 99%